Gerontologist skills and client satisfaction in long-term residential care for older persons - Pereira, Fernando A. (2017)
In contemporary Western societies the population aging poses new challenges both to the policies and to the support systems for the older persons. In Portugal, where the phenomena have a major impact, it hás emerged a new profeíisional profile, the gerontologist. Froin the beginning the gerontologist (Licenciates Diploma in Gerontology) hás emerged as a ncw professional exclusively devnted to providing care for the older persons and shares the labor market with other professionals who are usually leaders in LTCRs for the older persons, namely: managers, psychologists, nurses, sociologists, social educators and other social workers. Recent studies (Pereira &Antão, 2014; Pereira & Caria, 2014) showa clear evidencc oftechnical, organizational and communicative skills, which can be considered specific to this professional group (gerontologiíits) and which are distinctive from thüíie shown by other professional caregivers. Tlie focus goes to the sensibility of the gerontologists to detect in advance symptoms of a pathological aging, and to a personal contact with the older person and their families. It is still very valuable their ability to organize and develop innovative services and activities. The internalization of the concept ot interdisciplinary and the ability to integrate and streamline interdísciplinary technical teams is also mentioned as a feature of this professional group. These profile skills have been considered by employers the main reasons to hire gerontologists rather than other professiohals (Pereira, Mata & Pimentel, 2012). In this stady 160 older persons living in Portuguese LRTC are questioned abouí their satisfaction in regard to the effectiveness of organization. The older persons from LTRCs managed by a gerontologist are more ïikely to be "more satisfied with províded care. This association was not explained by residents characteristics or by the older persons circumstances as residents. ïhese findings highlight the appropriateness ofgerontologist skills in managing LTRCs.